Magnitude of Retranslocation of N, P, K in Populus deltoides intercropped with Mentha species - Mohsin, Afreen; Singh, Charan; Singh, Charan (Indian Forester, 2026)
This research has been done to study Re-translocation of N, P, K in intercropped Poplar with Mentha species. The clone of Populus deltoides is G-48 and the Mentha species used are Mentha arvensis, Mentha piperita and Mentha citrata. The annual litter production increased with increasing age of Populus deltoides plantations both in the pure and intercropped stands of Mentha species. An increase in litter production was recorded in all the intercropped stands in comparison to pure stands at all the ages. Higher concentration of N, P and K was observed in the litter of the intercropped stands which decreased with increasing ages of the pure stands. Nutrient concentration in green foliage, decreased with increasing ages of the stands. It was higher in the stands intercropped with Mentha spp. than the pure stands. Magnitude of Re-translocation (%) in pure as well as in intercropped plantation, increased with increasing ages of the stands.